Statistical optimization of adsorption processes for removal of 2,4-dichlorophenol by activated carbon derived from oil palm empty fruit bunches - Alam, Md. Zahangir; Muyibi, Suleyman Aremu; TORAMAE, J (Research Center for Eco-environmental Sciences,Chinese Academy of Sciences, 2007)
The adsorption capacity of activated carbon produced from oil palm empty fruit bunches through removal of 2,4-dichlorophenol from aqueous solution was carried out in the laboratory. The activated carbon was produced by thermal activation of activation time with 30 min at 800°C. The adsorption process conditions were determined with the statistical optimization followed by central composite design. A developed polynomial model for operating conditions of adsorption process indicated that the optimum conditions for maximum adsorption of phenolic compound were: agitation rate of 100 r/min, contact time of 8 h, initial adsorbate concentration of 250 mg/L and pH 4. Adsorption isotherms were conducted to evaluate biosorption process. Langmuir isotherm was more favorable (R2=0.93) for removal of 2,4-dichlorophenol by the activated carbon rather than Freundlich isotherm (R2=0.88)